Design of red-shifted and environment-sensitive fluorogens based on GFP chromophore core. (June 2020) - Smirnov, Alexander Yu.; Perfilov, Maxim M.; Zaitseva, Elvira R.; Zagudaylova, Marina B.; Zaitseva, Snizhana O.; Mishin, Alexander S.; Baranov, Mikhail S.
Abstract: Fluorescent staining is an indispensable method to study living systems. One of the recent fundamental advances in this field is the development of fluorogenic dyes - compounds that have no pronounced fluorescence in the free state but acquire it upon binding with the target object, allowing for simple no-wash labeling. Among these dyes, it is worth to note compounds whose fluorescence is particularly sensitive to the properties of the microenvironment (e.g., solvent), which can be used, for example, for staining cell organelles. In this paper, we present a novel technique for the creation of such environment-sensitive and red-shifted fluorogenic dyes with large Stokes shifts. Novel dyes are based on the GFP chromophore core and exhibit high solvent-dependent variation of emission maxima position and fluorescence quantum yield. These compounds are cell-permeable and rapidly stain the endoplasmic reticulum in living cells. Highlights: Novel red-shifted fluorogenic dyes based on the GFP chromophore are presented. Dyes demonstrated high solvent-dependent variations of the fluorescence quantum yield. Created compounds can be used for fluorescent staining of Endoplasmic Reticulum.